2023
DOI: 10.1097/mnh.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation: recent developments in clinical and preclinical research

Paul Drawz,
Daniel Baumann,
Alex Dayton

Abstract: Purpose of review Renal denervation represents a new dimension to hypertension treatment, with multiple device manufacturers seeking premarket FDA approval currently. Interest in the efficacy and safety of the treatment has spurred compelling mechanistic studies into the function of renal nerves and downstream impacts of denervation. Recent findings A trial of the ultrasound Paradise Catheter system (RADIANCE II) found a 6.3 mmHg reduction in SBP relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…1 Finally, the role of the sympathetic nervous system in hypertension is clinically supported by trials of catheter-based renal nerve ablation (CBRNA), which have demonstrated sustained reductions in arterial pressure in patients with drugresistant hypertension. 3 Along with decreased arterial pressure, CBRNA has also been reported to reduce skeletal muscle SNA, 4 episodes of sleep apnea, 5 and cardiac arrhythmias. 6 These findings led to the hypothesis that CBRNA may decrease arterial pressure by ablating sympathoexcitatory afferent renal nerves (ARNs) rather than, or in addition to, efferent renal nerves.…”
mentioning
confidence: 99%
“…1 Finally, the role of the sympathetic nervous system in hypertension is clinically supported by trials of catheter-based renal nerve ablation (CBRNA), which have demonstrated sustained reductions in arterial pressure in patients with drugresistant hypertension. 3 Along with decreased arterial pressure, CBRNA has also been reported to reduce skeletal muscle SNA, 4 episodes of sleep apnea, 5 and cardiac arrhythmias. 6 These findings led to the hypothesis that CBRNA may decrease arterial pressure by ablating sympathoexcitatory afferent renal nerves (ARNs) rather than, or in addition to, efferent renal nerves.…”
mentioning
confidence: 99%